Penyuluhan dan Pembinaan Unit Pengumpul Zakat (UPZ) di Desa Rahuning II Kecamatan Rahuning Kabupaten Asahan - Andri Nurwandri (Fusion: Jurnal Pengabdian kepada Masyarakat, 2022)
One of the causes of the low value of UPZ collection is that the UPZ institution is not yet accountable and optimal. Zakat institutions established by government officials at the rural level include the UPZ Institution of Rahuning II Village, Rahuning District, Asahan Regency. The purpose of this activity is to develop a Zakat Collecting Unit (UPZ) in Rahuning II Village through counseling on the management of accountable institutions. The implementation method used is counseling and mentoring. The counseling provided was in the form of counseling on bookkeeping, operational management, organizational transparency, UPZ UPZ consultants in Rahuning II Village. The results of the activity show that the understanding of the managers of the Zakat Collecting Unit at the Village level needs to be improved in terms of operational management and financial management. Extension activities in the development of the Zakat Collecting Unit in Rahuning II Village are still not optimal, so further counseling is needed.